Perception of general dentists and laypersons towards altered smile aesthetics - Amrita Geevarghese; Jagan Kumar Baskaradoss; Mohammed Alsalem; Abdulelah Aldahash; Waleed Alfayez; Tariq Alduhaimi; Abdullah Alehaideb; Omar Alsammahi (Wolters Kluwer Medknow Publications, 2019)
OBJECTIVES: This study aimed to evaluate how dental practitioners and laypersons differ in their perception of altered smile aesthetics based on viewing images of a digitally manipulated smile. MATERIALS AND METHODS: A photograph with close to ideal smile characteristics was selected and digitally manipulated to create changes in buccal corridor space (BCS), midline diastema, gingival display, and midline shift. These altered images were rated by two groups: dental practitioners and lay persons using a visual analogue scale. The mean ± standard deviation (SD) of both groups were calculated and the Student's t-test was used to identify any statistically significant differences between the groups. Data analysis was done using the Statistical Package for Social Science (version 23.0; SPSS Inc., Chicago, Illinois, USA). RESULTS: The dentists were more sensitive to changes in the midline shift than laypeople and provided lower scores. There were no significant differences between the two groups when the gingival display alteration was ≤3 mm. However, for gingival display of 4 mm and 5 mm, there was significant difference between the two groups, with dentist rating them poorer as compared with the laypeople (P < 0.001). Dentists were more sensitive than the laypeople for midline diastema of 2 mm and 3 mm (P < 0.001 and P = 0.005 respectively). Changes in the BCS had minimal impact on the overall esthetic score for both the groups. CONCLUSIONS: Perception of smile esthetics differed between dentists and laypersons.